Mapping the literature and prospective of ‘corporate social responsibility’ and ‘education’ vis-à-vis a bibliometric analysis - Arpit Sharma; Sanjeevi Shanthakumar (Revista on line de Política e Gestão Educacional)
The purpose of the research is to identify the present metrics in the field of Corporate Social Responsibility and education and to identify the metric of subject-wise distribution for analysing the interdisciplinary approach, keywords, country-wise distribution. The study uses the database of Scopus and applies a filter about the timeline from 1982 to 2021(ongoing factorial); filters out the segment in various disciplines, integrated with the field of CSR and education. The findings of the study are as follow: there is a constant increase in the contribution of CSR and education every year after 2000; there is an increase in contributions from various disciplines on CSR and education; and major contribution about the literature being done through articles; followed by book chapters, and book review. This study provides a perspective about CSR and education to future scholars about the existing metric of different disciplines. Provides a landscape on CSR and education.